Effect of pH on transport characteristics of silicon carbide nanowire field-effect transistor (SiCNW-FET) - TEKER, KAŞİF (SPRINGER, 2021)
This paper investigates the effect of pH on transport properties of silicon carbide nanowire field-effect transistor (SiCNW-FET) including the key parameters such as transconductance, resistivity, stability, and repeatability of the device towards harsh environment-sensing applications. Transport properties were investigated under different pH solutions ranging from pH 5 to pH 9. The device exhibited a high transconductance of 4.5 mS and a very low resistivity of 0.065 m omega cm at pH 5 at a bias voltage of 2 V. The device showed an increase in conductance (from 2.66 to 4.5 mS) after applying the solution with pH 5 and then a substantial decrease in conductance (from 4.5 to 0.15 mS) with increasing the pH from 5 to 9 was observed. The changes in conductance can be attributed to the metal oxide/electrolyte binding sites model and to the hydrogen ions adsorption on the surface of the SiC nanowires altering the total surface charge density. The device exhibited almost a full recovery after rinsing with DI water, achieving good stability and repeatability. In consequence, this study would contribute to the development of low-power and cost-effective 3C-SiCNW-based FETs for use in the fields of bio- and environmental sensing, as well as biomedical applications.